Female Judges in Malaysian Shariʿa Courts: A Problem of Gender or Legal Interpretation? - Mohd Zin, Najibah (Brill, 2017)
Over the past decades, concern for wider recognition of female participation in the shari‘a judicial service has been growing as a result of dissatisfaction with court orders pertaining to family matters. Blame is often ascribed to inefficient court officials, who are accused of failing to deal sensitively with predominantly female petitioners. Such concerns led to the appointment of the first female judges to the shari‘a courts in 2010. However, in the majority of states, the overall procession of the appointment of female judges to shari‘a courts remains slow and contested. This study therefore examines issues related to the appointment and the role of female judges in the Malaysian shari‘a courts. It presents a qualitative analysis of the public debates on this issue as well as interviews with female judges, and thus determines the main obstacles to the appointment of female court officials in the religious courts.